(untitled) (Journal of Applied Learning and Teaching, 2023)
By using standardised approaches, systematic reviews of the educational, scientific literature can inform educational research and influence educational policies and practices. However, the various systematic reviews of the scientific literature in the field of Artificial Intelligence (AI) and education all adopt individual approaches, making it challenging to systematically compare their conclusions. Accordingly, this paper presents a standardised protocol for conducting systematic reviews of the scientific literature on AI and education (AI&ED), including both literature on teaching and learning with AI (AIED) and literature on teaching and learning about AI (AI literacy). Our protocol applies the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and is presented here for the purpose of replication and validation. We exemplify our protocol by means of a systematic review of the scientific literature on trustworthy and ethical AI&ED, which was undertaken iteratively in symbiosis with the development of the protocol, informing each other throughout. In the future, we intend to apply our novel protocol for other search terms of relevance to AI&ED, as well as for the same search terms over a longer time period, in order to allow comparisons and the exploration of trends.